ANALISIS KEPUASAN PEMILIK KAPAL TERHADAP PENGURUSAN CLEARANCE KEBERANGKATAN KAPAL NELAYAN DI PT. PUTRA BUKIT RAYA LINE UNTUK WILAYAH PENANGKAPAN DI LAUT KARIMUN - Abdul Aziz Yulianto; Tri Mardalena; Mey Krisselni Sitompul (JURNAL JALASENA, 2023)
This study aims to determine the assessment of customer / ship owner satisfaction, of the performance carried out by PT Putra Bukit Raya Line in managing the clearance of departure of fishing boats in the Karimun Sea. The subjects in this study were 30 customers / ship owners, to assess the performance carried out by PT Putra Bukit Raya Line in carrying out clearance management services, which were authorized by customers / ship owners to the ship agency company. The selection of the subject of this research is based on customer satisfaction / shipowners at PT Putra Bukit Raya Line. Based on the results showed, the quality of service between the percentage interval on the independent variable X quality of clearance management services 89.12%, and the dependent variable Y customer satisfaction / shipowner 89.06% at PT Putra Bukit Raya Line in accordance with the descriptive percentage criteria 81% - 100%, with the category strongly agreeing on the quality of clearance management services. The research results from each dimension show that the physical evidence dimension (Tangible) is the dimension that has the smallest quality value, while the largest quality value is in the empathy dimension (Empathy).